Avaliação da exposição ocupacional de agentes da PRF da região Norte do estado do Mato Grosso a inseticidas inibidores da colinesterase - Bonache, Juliandra Spagnol (2022)
Occupational toxicology has the principle of preserving the health of the worker and preventing adverse effects that may be caused by exposure in the work environment. In order to support the integrity of health of workers, Brazilian legislation has the occupational health medical control program (PCMSO), regulated by Regulatory Norm number 7 (NR7). The world scenario presents great agricultural production to meet the needs arising from the constant population growth. Brazil has reached the ranking of the largest pesticide market in the world since 2008 and the state of Mato Grosso is the largest consumer of pesticides in Brazil. Insecticides that are intensively used, organophosphates (OP) and carbamates (CB), are inhibitors of cholinesterase enzymes causing hyperstimulation of their biological effects. Thus, the objective of this study was to evaluate the exposure of federal highway police (PRF) agents to cholinesterase inhibitor, through biological monitoring recommended by NR7 and clinical evaluation to verify occupational overexposure. The assessment of occupational exposure followed that recommended by NR7 with assessment of blood cholinesterases in pre- and post-occupational moments. The results showed inhibition of cholinesterase activity in the post-occupational period with mean and standard deviation of 33.27 ± 19.10 (%) for butyrylcholinesterase (BChE) and 29.86± 16.10 (%) for acetylcholinesterase (AChE). It was also evidenced that four volunteers presented BChE inhibition above the limit recommended and six volunteers presented AChE inhibition above the limit recommended by NR7. Pulsation was statistically higher in the post-occupational period. The parameters of systolic and diastolic pressure showed a slightly higher mean in the post-occupational period, but without statistical difference. Neurobehavioral signs were evaluated through the MMSE and MINI (DSM-V) tests and no statistical differences were detected. The results of the present study show that there are significant biochemical changes, but that have not yet led to neurobehavioral changes. This fact may be associated with the shorter working time in the northern region of the state of Mato Grosso, manifested by most volunteers. It was possible to verify that the real working conditions of this population are challenging and the need for constant monitoring becomes indispensable.